Respuesta :

A.

Firstly, you should deal with the inner function.

1^2 - 1 = 0

And

2 x 0 = 0

So 2g(1) = 0

Applying the outer function:

0 + 1 = 1

For this case we have, that given two functions f (x) and g (x), then:

The composite function of f with g is: [tex](gof) (x) = g [f (x)][/tex]

The function composed of g with f is: [tex](fog) (x) = f [g (x)][/tex]

In this case we have:

[tex]f (x) = 1 + x\\g (t) = t ^ 2-1[/tex]

First we solve g (1):

[tex]g (1) = 1 ^ 2-1 = 0[/tex]

Now:

[tex]2 * g (1) = 2 * 0 = 0[/tex]

Then we have left:

[tex]f (0) = 1 + 0 = 1[/tex]

So, we have to:

[tex]f (2g (1)) = 1[/tex]

Answer:

Option A

ACCESS MORE